Examining EFL teachers’ knowledge, attitudes and perceived practices of differentiated instruction in English classrooms - Aragaw Delele Endeshaw (Jurnal Cakrawala Pendidikan, 2023)
The predominant intention of this study turned into to investigate English language teachers' knowledge, attitudes, and perceptions of differentiated guidance in English training at some decided on trendy secondary colleges in Ethiopia's Amhara Region. A combined studies layout turned into used to perform this purpose. Using a scientific sampling technique, forty-five grade 9 English language teachers from Dangila, Chagni, Tilili, BahirDar, and Gondar trendy secondary colleges had been selected as participants. Data turned into accumulated via interviews, questionnaires, and observation. The statistics found out that English language instructors had a excessive information of differentiated education, however little exercise with it. Teachers had a poor mindset closer to differentiated education, consistent with the findings. Furthermore, big elegance sizes, time constraints, a loss of determination and motivation because of inadequate remuneration, activity disappointment because of unmotivated college students had been all noted as deterrents to DI implementation in EFL lecture rooms at colleges. Finally, after thinking about the findings, pointers were made.